Environmental Uncertainty and Manager's Personnel Value Effect on Environmental Disclosure - Fuadah, Luk Luk; Saftiana, Yulia; Kalsum, Umi (Jurnal Organisasi dan Manajemen, 2021)
This study aims to examine the effect of environmental uncertainty and managers' personnel value on environmental disclosure. This study uses a saturated sampling of manufacturing companies listed on the Indonesia Stock Exchange, and the respondents are all managers’ levels. The total sample of this study is 161 manufacturing companies. The respondents got the questionnaires via email, and 64 respondents completed them. These can be processed using the Structural Equation Model - Partial Least Square. Findings. The result shows that environmental uncertainty and managers' personnel value have a positive effect on environmental disclosure. Furthermore, this result shows that the manager's personnel value is the most dominant influence of environmental disclosure. These research findings add to the literature, especially about environmental disclosure, and support contingency theory and structuration theory. The findings can give information especially environmental disclosure for the manufacturing companies in Indonesia Stock Exchange. The policymaker should concern about environmental disclosure for companies listed on Indonesia Stock Exchange. The limitation of this research is the low response from the respondents of the research. Another limitation is related to R- Square's results, which still need further research.